The long-run effects of parental unemployment in childhood - James Uguccioni (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2022)
Parental job loss is a large, negative shock to the household that can affect children in both the short- and long-run. Little is known, however, about how the long-run impacts of job loss on children vary with the child's age at the time of displacement. This paper provides the first empirical evidence of the long-run effects of parental unemployment on children exposed before age 10 (and as young as 2), a period thought to be critical for child development. Using administrative tax data covering the universe of children born in Canada between 1972 and 1985 and random forest proximity matching, I estimate the causal effects of parental job loss experienced at different points in childhood on a child's income attainment. I find that children exposed to parental unemployment at ages 2 to 10 experience losses of 3 to 4 rank points in average earnings attainment in adulthood (approximately 2,500 per year). These children are also 36% more likely to receive welfare as adults and 4% less likely to pursue post-secondary education. Consistent with critical periods of child development, children who experience parental job loss before age 10 experience larger reductions in income attainment than children exposed at older ages. Decomposing these estimates, I show that the majority of my treatment effects are attributable to the timing of income losses experienced during childhood, as well as unemployment-induced moves to neighourhoods with less opportunity.
Keywords: 330; Arbeitslosigkeit; Eltern; Haushaltseinkommen; Kinder; Kausalanalyse; Kanada